KARAKTERISTIK PENDIDIKAN IMAN DALAM PENTAKOSTALISME - Amos Hosea (Bethel Press, 2019)
The characteristics of faith education in Pentecostal churches are described in this paper. Characteristics that emphasize the process of discipleship in the church, education that produces new leaders, education that creates church growth, education that is called the new apostolic church pattern and non-formal education are described in the nature of this paper. These five characteristics became the basis for Pentecostalism to develop into a church denomination that has grown quite rapidly to date.